Capacity maximisation of the secondary link in cognitive radio networks with hybrid spectrum access strategy - Tan, Xiaobo; Zhang, Hang; Hu, Jian (IET communications, 2014)
A hybrid spectrum access strategy which is different from traditional underlay or overlay strategy is proposed. In this strategy, the secondary users cooperatively sense the states of the primary users in the sharing spectrum band. Based on the sensing results and an additional requirement on the bit error rate, the secondary transmitter adapts its transmit power and modulation level. Specifically, if the primary user is detected to be inactive, the secondary transmitter allocates its power subject to a peak transmit power constraint. Else if the primary user is active, the average interference power constraint would also be imposed to protect the primary transmission. To demonstrate the superiority of the hybrid strategy, capacity of the secondary link with this strategy over Rayleigh fading channel is studied. It has been assumed that diversity combing technique is available at the secondary receiver. Perfect and imperfect estimations of the channel power gain from secondary transmitter to primary receiver are also considered. Then the expression of capacity of the secondary link is derived by using Lagrange dual decomposition method. Simulation results demonstrate that the capacity of the secondary link with hybrid strategy is significantly improved when compared with the traditional ones.